Problems and Prospects of Cross-Border Cooperation in Ukraine - PARKHOMENKO, V. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2021)
The purpose of the article is to analyze the current state of cross-border cooperation in Ukraine, characterize the main problems and outline the prospects for its development. The article considers the importance of cross-border cooperation for Ukraine, which consists in the possibility of solving common economic, cultural and environmental problems with the border regions of neighboring countries, attracting foreign capital, creating new jobs, equalizing territorial disparities in development. The history of formation of cross-border cooperation in the country is analyzed. It was found that the first Euroregion in Ukraine, the Carpathian one, was established in 1993, and in 1996 Ukraine became a member of the Tacis CBC Cross-Border Cooperation Program. The composition of the legal framework for the regulation of cross-border cooperation is studied, the conclusion is made about the declarative nature of state programs for its development. The problems hindering the development of cross-border cooperation in Ukraine are described. The main ones are the following: insufficient financial support for the implementation of cross-border cooperation projects and programs; insufficient level of project management quality at the level of subjects and participants of cross-border cooperation; inefficient use of borrowed funds; lack of official statistical information in the field of cross-border cooperation. Perspective directions of development of cross-border cooperation in Ukraine are outlined, among which it is necessary to allocate: creation of the uniform scientifically substantiated concept of cross-border cooperation of Ukraine with the EU member states which would consider the general European and national priorities; developing a clear mechanism for raising funds at the national level to ensure cross-border cooperation programs; improving existing mechanisms for obtaining and using EU technical assistance; intensification of formation and development of cross-border clusters.